IMPROVING STUDENTS’ SPEAKING SKILL BY USING STORYTELLING TECHNIQUE AT THE ELEVENTH GRADE STUDENT OF SMA TUT WURI HANDAYANI MAKASSAR - Yahuda Lohing; Muliaty Ibrahim; Sujarwo (FAKULTAS KEGURUAN DAN ILMU PENDIDIKAN UNIVERSITAS MEGAREZKY, 2022)
The aim of this study was to improving the students’ speaking skills by using storytelling technique at the eleventh grade student of SMA Tut Wuri Handayani Makassar that consist of 2 students. This research was classroom action research which was implemented in two cycle such as cycle 1 and cycle 2. On each cycle, there were four meetings consist of planning, action, observation and reflecting. The collecting data method used quantitative and qualitative data. Quantitative is the main data while qualitative is supporting data. Quantitative data consisted of speaking tests while qualitative data consisted of observation checklist, interviews, field notes, and documentation. The result showed that the using of storytelling technique can improve the students’ speaking skill. This could be proven through the average score of students in class XI. In cycle 1 was 72,76% while in cycle 2 was 82,36%. The result of percentage of completeness criteria also increased. In cycle 1, there were 14 students (56%)while in cycle 2 there were 25 students (100%). It showed that the use of storytelling technique could improve the students’ speaking skills.